Green Purchase Intention of Generation Z in Indonesia: An Extended Model Theory of Planned Behaviour - Vigory Gloriman Manalu (International Journal of Management, Economic, Business and Accounting, 2026)
Purpose of the study — This research aims to determine the interest in purchasing green products in Indonesia, especially among the younger generation. Research method— This research will use a quantitative approach. Primary data collection will use surveys via online and offline questionnaires. The research model will be tested on Generation Z. From the questionnaires distributed, 374 eligible questionnaires were collected for processing, with details of 130 questionnaires in offline form and 244 questionnaires in online form. To test the model and hypothesis, Structural Equation Modeling (SEM) will be used by presenting confirmatory factor analysis (CFA) to measure loading factor, average variance extracted (AVE), and composite reliability (CR) to meet predetermined Goodness of Fit (GoF) standards. Result— Social media information was found to positively and significantly affect green purchase intention. Social media information has a positive influence on subjective norms in Gen Z. Subjective norms positively influence the intention to purchase green products. This research finds subjective norms positively influence moral norms in Generation Z. Moral norms positively influence Generation Z's green purchasing interest Conclusion— These findings show that purchasing green products will be considered a personal contribution to something better. First, this research only focuses on Generation Z in the West Java region, which can be developed in other areas. Second, the number of respondents who filled out the questionnaire was limited. It is hoped that future research can develop this research model using theories related to environmental issues. Social media will play an important role in green products sold to Generation Z because they actively use social media to search for information. Maximizing social media use will indirectly increase subjective and moral norms, ultimately improving the intention to purchase green products in Indonesia. The novelty offered by this research is analyzing the relationship between social media variables and moral norms as antecedents of subjective norms and green purchasing intentions.